2015
DOI: 10.2139/ssrn.2618058
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Moving to a Territorial Tax System on Profit Repatriation: Evidence from Japan

Abstract: In an increasingly globalized world, the design of international tax systems in terms of taxation on foreign corporate incomes has received much attention from policymakers and economists alike. In the past, Japan's worldwide tax system taxed foreign source income upon repatriation. However, to stimulate dividend repatriations from Japanese-owned foreign affiliates, Japan introduced a foreign dividend exemption in 2009 that exempts dividends remitted by Japanese-owned foreign affiliates to their parent firms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Several empirical papers find support for tax deferral, by showing that US MNCs increase their dividend payout in response to lower taxes on repatriation (Hines and Hubbard, 1990;Altshuler and Newlon,1993;Grubert,1998;Altshuler and Grubert, 2003). Recent studies, exploiting UK's and Japan's adoption of a territorial system in 2009 in a quasi-experimental setting, provide similar evidence that exemption of foreign earnings boosted dividend repatriation in the UK (Egger et al, 2015) as well as in Japan (Hasegawa and Kiyota, 2017).…”
Section: Tax Deferralmentioning
confidence: 86%
“…Several empirical papers find support for tax deferral, by showing that US MNCs increase their dividend payout in response to lower taxes on repatriation (Hines and Hubbard, 1990;Altshuler and Newlon,1993;Grubert,1998;Altshuler and Grubert, 2003). Recent studies, exploiting UK's and Japan's adoption of a territorial system in 2009 in a quasi-experimental setting, provide similar evidence that exemption of foreign earnings boosted dividend repatriation in the UK (Egger et al, 2015) as well as in Japan (Hasegawa and Kiyota, 2017).…”
Section: Tax Deferralmentioning
confidence: 86%
“…In addition, the Japanese taxation system changed from the territorial system to the personal link system. Hasegawa and Kiyota (2013) observed that Japanese overseas affiliates exhibited varying responses to this change. In the past ten years, Japanese outward FDI in China and the number of Japanese FDI affiliates in China have changed substantially compared with Taiwanese businesses.…”
mentioning
confidence: 99%
“…These effects occurred even though (prereform) UK rules allowed greater scope for UK MNCs to return cash to the parent via mechanisms that avoided the repatriation tax than is the case for US MNCs. Hasegawa and Kiyota (2015) find similarly that repatriations from foreign affiliates with large amounts of retained earnings increased after the Japanese reform.…”
Section: 1) Evaluating "Consensus" Reformsmentioning
confidence: 68%